Produção de citocinas IL-1,IL6 e CXCL8 por explantes endometriais de novilhas azebuadas estimuladas por diferentes padrões moleculares associados a patógenos - Philipe Pimenta Nunes (2017)
The objective of this study was to evaluate the production of proinflammatory cytokines interleukin 1 (IL1), interleukin 6 (IL6) and chemokine CXCL8, by endometrial explants of zebu based heifers at diestrous stimulated by pathogen-associated molecular patterns and the influence of different phases of the estrous cycle on such production. The cytokines concentrations in culture medium were measured by ELISA. Endometrial explants were stimulated by different concentrations of lipopolysaccharide (LPS), synthetic triacetylated lipoprotein (PAM3) and peptideoglycan (PGN). The production dynamics, the cytokines accumulation over time and the cytokines production by endometrial explants from genital tracts at different phases of the estrous cycle were evaluated by stimulation with 1.0 g/mL of LPS. Endometrial explants produced higher concentrations of IL1 in response to 1.0 g/mL of LPS (P<0.05) after 24 hours of culture and 10.0 g/mL of PGN (P<0.01) after 24 and 48 hours of cultivation; higher concentrations of IL6 in response to 0.1 (P<0.05) and 1.0 g/mL of LPS (P<0.01) and CXCL8 in response to 0.1 (P<0.01) and 1,0 g/mL LPS (P<0.01) after 24 hours of culture. LPS-stimulated explants showed higher IL1 production at 6 to 12 and 12 to 18 hours (P<0.05), with higher accumulation after 24 hours of culture (P<0.05); increased IL6 production during the first 12 hours of culture (P<0.05), accumulating higher concentrations of IL6 after six (P<0.01) and 24 hours (P<0.05) of culture; greater production of CXCL8 at 6 to 12 and 18 to 24 hours (P<0,05), with significant accumulation from 6 to 48 hours (P<0.05) of culture. LPS-stimulated endometrial explants from metaestrous phase genital tracts produced higher concentrations of IL6 (P<0.01) and CXCL8 (P<0.05) after 24 hours of culture and IL6 (P<0.05) after 48 hours of cultivation. Endometrial explants of diestrous phase genital tracts produced higher concentrations of IL1 (P<0.05), IL6 (P<0.05) after 24 hours of culture and IL6 (P<0,05) after 48 hours of cultivation. On the other hand, endometrial explants from proestrous/estrous genital tracts produced higher concentrations of IL1 (P<0.05) after 24 hours of cultivation. There was no significant difference in cytokine production by endometrial explants from genial tracts at different stages of the estrous cycle. In conclusion, endometrial explants of zebu based heifers at diestrus phase respond to stimulation by PAMP with production of IL1, IL6 and CXCL8 and phases of the estrous cycle do not influence the production of proinflammatory cytokines by LPS-stimulated explants.